Interactive effects of combined manganese and microplastic pollution on soybean growth - Ren, Jun; Luo, Xuqiang; Luo, Yang; Xu, Xiuyue; Wang, Qian; Zhang, Qifang (Frontiers in Plant Science, 2025)
Soil microplastics (MPs) and heavy metals pose a threat to agricultural production. Excessive manganese (Mn) can be toxic to plants. The impacts of combined MP and Mn pollution in soil on plant growth are poorly understood. This pot experiment systematically investigated the effects of single or combined pollution by polyethylene microplastics (PE-MPs) at different concentrations (0%, 0.50%, and 1.5%) and Mn (MnSO4, 0%, 0.25%, and 0.50%) on soybean growth. The addition of Mn + PE-MPs significantly reduced soil pH; PE-MPs increased soil organic matter (OM), while Mn (0.25%) + PE-MPs significantly decreased soil OM. Both single and combined additions of Mn and PE-MPs significantly reduced soil available nitrogen and available phosphorus, but increased soil available potassium. Polyethylene microplastics decreased the number of soybean root tips, whereas Mn (0.25%) resulted in a significant increase. Soybean biomass was highest under the Mn (0.25%) + PE-MPs (0.50%) treatment. PE-MPs significantly increased the peroxidase, catalase, and superoxide dismutase activities in soybeans, while Mn (0.25%) significantly reduced their activities. The addition of low concentrations of Mn alleviated the PE-MP stress on soybeans and exerted a detoxifying effect. These findings provide scientific support for the safe production of soybeans.